Innovation of the Reproductive Health Class “Eskimo Class” on Adolescents’ Knowledge About Reproductive Health in Padang City - Iffah, Uliy; Fitrayeni, Fitrayeni; Rachim, Dyan Permata; Rahmadhini, Zikra; Hayfa Syafiyyah, Nasywa (Riviera Publishing, 2025)
Introduction: Adolescence is the time between childhood and maturity, usually between the ages of 10 and 19 years. According to the Data and Information Center of the Indonesian Ministry of Health, the number of adolescents in Indonesia is estimated at around 45.35 million people, or about a quarter of the total population. In Padang City itself, the number of adolescents reached 178,402 people. The adolescent age group is at high risk for reproductive health problems including premarital sexual behavior, drugs and even HIV/AIDS. The government has paid attention to adolescent problems by establishing the Adolescent Health Care Service (PKPR) program at health centers. The results of the evaluation of the PKPR Program in 2016 in the Andalas Health Center Working Area of Padang City showed that this program had not been implemented optimally. Therefore, it is necessary to carry out innovations related to reproductive health in adolescents in the form of the establishment of a Comprehensive Reproductive Health Class (Eskimo Class). Objective: To determine the effectiveness of Eksimo Class in increasing adolescent knowledge about reproductive health. Method: The research design used was a quasi-experimental with a one group before and after design. In this research design, the sample will be given a pre-test first, then given an intervention, and a post-test in 1 group without a control group. The study was conducted in April-November 2024 in the Andalas Health Center Working Area, Padang City. Results: An average of 17.21, or about 81.9%, was the students' knowledge of reproductive health prior to receiving health education, and 18.13, or approximately 86.3%, was the students' knowledge afterwards. Conclusion: The Asymp value was derived from the statistical test. Sig 0.051 > ?0.05 so it is concluded that there is no effect of health education on the level of adolescent knowledge about reproductive health because the average value before and after the intervention only increased by 4.4%.